Photoredox-catalyzed arylation of isonitriles by diaryliodonium salts towards benzamides; Beilstein Journal of Organic Chemistry; Vol. 21 - Metalnikova N. M. Nadezhda Maksimovna; Antonkin N. S. Nikita Sergeevich; Tuan K. Nguyen; Soldatova N. S. Nataliya Sergeevna; Nyuchev A. V. Alexander; Kinzhalov M. A. Mikhail Andreevich; Postnikov P. S. Pavel Sergeevich (2025, 2025)
Title screen